Power of the Court to Alter the Company Constitution According to Shareholders’ Agreement - Oon, John Chuah Chong; Jaiman, Cartaz Ummu Syawaeda bt; Basir, Sayidah Asma; Kuppanan, Krishnan A/L (Journal of Accounting, Business and Management (JABM), 2024)
Members of a company can vote in general meetings to alter the company’s constitution. The courts can also alter the company’s constitution under section 37(1) of the Companies Act 2016. The problem is that of statutory construction. A literal interpretation means altering the contents of the constitution without voting. A purposive construction entails an alteration of the quorum or procedures to facilitate proper voting. The objective of this paper is to ascertain how the Malaysian courts exercise that power. A comparative research methodology involving a legal doctrinal analysis is employed. Primary and secondary sources of law throughout the commonwealth countries are ascertained as to the effect of the law on the research objectives. The findings reveal that alteration by the court entails a direct alteration of the constitution and not the procedures therein to facilitate proper voting. In the absence of oppression, an alteration is possible to satisfy the legitimate business or management expectations of members, according to a shareholders' agreement. This is true in private companies where shares cannot be transferred to outsiders and quasi-partnership companies. Retrospective alteration and alteration that affects third-party rights cannot be made in the event proper voting can be executed under the existing constitution.